The Influence of Workload and Physical Work Environment as Predictors of Work Stress among Employees at the Salatiga City Education Office - Utami, Elsiwi Sobat; Kristianingsih, Sri Aryanti (Amkop Management Accounting Review (AMAR), 2025)
Work stress is a condition of tension that affects emotions, thought processes, and physical condition in the work environment. The purpose of this study was to examine workload and physical work environment simultaneously as predictors of work stress among employees of the Education Department of Salatiga City. This research employed a saturation sampling technique involving the entire population of 62 employees as the research sample and utilized multiple linear regression analysis for data processing. The results showed that there was a significant influence of workload and physical work environment together as predictors of work stress among employees of the Education Department of Salatiga City, with a contribution of 92.2%. Specifically, both workload and physical work environment demonstrated significant effects on work stress. Based on categorization, the majority of respondents were at moderate levels for all three variables studied. This means that the higher the workload and the less conducive the physical work environment, the higher the level of work stress experienced by employees, and vice versa.